Corruption and internet governance. Issue 2 (4th March 2014) - Sutherland, Ewan
Abstract : Purpose: – The purpose of this paper is to review the extent and the manner in which internet governance systems could and do engage with the problems of potential and actual corruption. Design/methodology/approach: – A review of internet multistakeholder systems and their compatibility with global best practice in countering corruption. Findings: – The multistakeholder systems contain systemic weaknesses, exposing them to risks of corruption and capture that would be very difficult to identify and eradicate. Practical implications: – A number of opportunities are identified to improve resilience of internet multistakeholder systems against the dangers of capture and corruption. Originality/value: – There is no research published on this topic.